Endometriosis within the sigmoid colon associated with hematochezia in a hysterectomized woman - Ulloa-Ortiz, Óscar (2018)
Endometriosis is the presence of functional ectopic endometrial tissue outside the uterine cavity. The clinical presentation is variable and depends on the location. It is considered the third leading cause of hospitalization in the United States. In this case, we report a 44-year-old woman with hematochezia caused by deep infiltrating endometriosis within the sigmoid colon, after having undergone a hysterectomy 11 years ago. The patient received surgical resection due to suspicion of carcinoma.